Synthesis, characterization and assessment of the cytotoxic properties of cis and trans-[Pd(L)(2)Cl(2)] complexes involving 6-benzylamino-9-isopropylpurine derivatives - Trávnícek, Zdenek; Szucová, Lucie; Popa, Igor (Journal of inorganic biochemistry, 2007)
A series of square-planar Pd(II) complexes of the composition cis-[Pd(L(n))(2)Cl(2)] {L(1)=2-chloro-6-benzylamino-9-isopropylpurine (1), L(2)=2-chloro-6-[(4-methoxybenzyl)amino]-9-isopropylpurine (2), L(3)=2-chloro-6-[(2-methoxybenzyl)amino]-9-isopropylpurine (3) and 2-[(chloropropyl)amino]-6-benzylamino-9-isopropylpurine (6)} has been synthesized by the reaction of PdCl(2) with L(n) in a 1:2 molar ratio. In contrast, the same reaction followed by recrystallization of the product from N,N'-dimethylformamide (DMF) leads to trans-[Pd(L(n))(2)Cl(2)] x nDMF {L(3), n=0 (4), n=1(4( *)DMF); L(4)=2-chloro-6-[(2,3-dimethoxybenzyl)-amino]-9-isopropylpurine, n=0 (5), n=1.5 (5( *)DMF). The compounds have been characterized by elemental analyses, conductivity measurements, electrospray mass spectra in the positive ion mode (ES+MS), FTIR, (1)H and (13)C NMR spectra, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Moreover, the complexes 2 and 6 have been also investigated by (15)N NMR spectroscopy. The molecular structures of L(5), {(H(2+)L(5))(Cl(-))(2)} x H(2)O, i.e. the protonated form of L(5), trans-[Pd(L(3))(2)Cl(2)] (4) and trans-[Pd(L(4))(2)Cl(2)] (5) have been determined by single crystal X-ray analysis. NMR data and X-ray structures revealed that the organic molecules are coordinated to Pd via N7 atom of a purine moiety. All the complexes and the corresponding ligands have been tested in vitro for their cytotoxicity against four human cancer cell lines: breast adenocarcinoma (MCF7), malignant melanoma (G361), chronic myelogenous leukaemia (K562) and osteogenic sarcoma (HOS). Promising in vitro cytotoxic effect has been found for cis-[Pd(L(2))(2)Cl(2)] (2), having the IC(50) values of 12, 10, 25, and 14 microM against MCF7, G361, K562, and HOS, respectively, and for trans-[Pd(L(3))(2)Cl(2)].DMF (4) with the IC(50) value of 15 microM against G361.
Keywords: Purines; krystalografie rentgenová; protinádorové látky; Cell Line, Tumor; Drug Screening Assays, Antitumor; molekulární struktura; Molecular Structure; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; puriny; Inhibitory Concentration 50; Organometallic Compounds; molekulární modely; Crystallography, X-Ray; Models, Molecular; lidé; Humans; Spectrometry, Mass, Electrospray Ionization; nádorové buňky kultivované; screeningové testy protinádorových léčiv; hmotnostní spektrometrie s elektrosprejovou ionizací; Tumor Cells, Cultured; inhibiční koncentrace 50; nádorové buněčné linie; Antineoplastic Agents; organokovové sloučeniny